A novel “conceive, design, implement, operate (CDIO)” framework for evaluating artificial intelligence–generated scholarly manuscripts - Aji Prasetya Wibawa; Anik Nur Handayani; Prananda Anugrah; Agung Bella Putra Utama (Science Editing)
This paper introduces a novel application of the “conceive, design, implement, operate (CDIO)” framework to improve the thoroughness and organization of academic editorial review processes. It demonstrates that the CDIO framework, originally applied to engineering education, can also be adapted for reviewing creative and interdisciplinary ideas. The adaptation of the CDIO framework for editorial review is already evident in scholarly publications, and this paper extends its application to include reviews of content produced by artificial intelligence (AI) platforms. The “conceive” stage focuses on developing clear research questions and objectives that align with the key moments of article conception. It ensures that content produced by AI begins with an ethical scientific foundation and maintains this integrity throughout the process. The “design” stage emphasizes maintaining scientific accuracy and clarity of presentation. It considers all critical manuscript design elements and incorporates methods to evaluate the originality and rationality of AI-generated data and analysis. The “implementation” stage is concerned with the effective communication of findings, providing insights into how the manuscript is perceived. It is crucial for data generation or tool usage involving AI. The “operate stage” involves analyzing the findings and their overall impact on the field, ensuring a comprehensive assessment from all perspectives when AI-generated content is integrated into academic discourse, which has broader implications. By applying the CDIO framework innovatively, this paper offers a systematic and comprehensive method for conducting editorial reviews. This ensures that manuscripts generated by AI are subjected to the same rigorous scrutiny as those authored by humans. This approach improves the quality, transparency, and reputation of scholarly publications. We examine each stage of the CDIO process, achieving uniformity and clarity, and providing a more precise evaluation of both traditional and AI-assisted academic research.